Familial monophasic acute transverse myelitis due to the pathogenic variant in VPS37A. (February 2018) - Mealy, Maureen A.; Nam, Tai-Seung; Pardo, Santiago J.; Pardo, Carlos A.; Sobreira, Nara L.; Avramopoulos, Dimitrios; Valle, David; Burns, Kathleen H.; Levy, Michael
Abstract : Objective: To identify genetic differences among siblings with a family history of idiopathic transverse myelitis (ITM). Methods: We compared whole-exome sequencing (WES) on germline samples from the 2 affected sisters with ITM with 3 of their healthy siblings. Results: The 2 sisters with ITM both had acute onset of sensory loss in the legs, weakness, and bowel/bladder dysfunction. The first developed ITM at age 15 years with a clinical nadir of complete paralysis, which slowly recovered over a few years. MRI demonstrated a persistent T2 lesion in the lower thoracic cord. The second developed ITM at age 50 years with a nadir of sensory loss from T6 down and paraparesis in the legs, associated with an MRI lesion at T6. She also made a partial recovery with treatment. Both sisters are homozygous for a missense variant in VPS37A (c.700C>A, p.Leu234Ile) identified by WES. We performed targeted sequencing of VPS37A in an additional 86 samples from patients with ITM and 175 with other diseases to investigate the p.Leu234Ile variant. We identified another patient with ITM homozygous for the same rare variant. No patients with multiple sclerosis, neuromyelitis optica, other neurologic conditions, or any healthy controls in public databases were homozygous for this variant. Conclusions: A rare missense variant in VPS37A may predispose to development of ITM. Further studies are necessary to determine the frequency of this variant in the patient population and the mechanism through which it contributes to the risk of disease.